Psychological problems and challenges among students at Sultan Qaboos University - Hamed Al-Wahshi, Salwa Khalifa; Ismail, Nik Ahmad Hisham; Shehu, Fatmir Mehdi (OCERINT International, 2021)
The objectives of this study is to investigate the students’ challenges and problem at Sultan Qaboos University, the impacts of those challenges and problems on students' lives, and setting up a group counseling program to treat those problems that students face at the university and provide them with the necessary skills. The sample space of this inquiry is confined to members of the student counseling center at SQU. The study employs qualitative and quantitative research methodology to define the research problem. The data is collected using an interview tool, where the researcher has interviews with counselors and four students at the student counseling center, as well as interviews with four psychologists. The analysis deployed in the discussion tries to relate the data and its findings to the hypothesis of the thesis. The study analysis shows several problems and challenges facing students of SQU and reveals its clear impacts on students' expectations during university years, and their future as well. Consequently, the finding shows that students of SQU face many psychological, academic, social, and financial challenges at the university. Also, the study indicates those students' challenges during university life. The students most exposed to pressures and challenges are those of the foundation year. The study also revealed that one of the most important challenges that students face is the academic life and compatibility with the university’s academic system, and adaptation to university life, which has emerged as the biggest psychological problems that students facing. The results show the transportation problem as a challenge student face when joining the university. The interviews conducted by the researcher show the importance of expectations in students' lives, as they are the ones that motivate and push students to achieve their goals. Based on the findings of the study, the researcher establishes a set of recommendations, the most important of which is to design a proposed counseling program for the student counseling center of SQU to provide students with the necessary skills that help in coping with their daily problems and challenges that they may face in the future, thus contributing to reducing those challenges impacts on their future expectations.